A negative electrode sheet, a secondary battery, and an electronic device
Patent Information
- Application Number
- CN202510563481.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2026-10-30
AI Technical Summary
[0004]本申请的目的在于提供一种负极极片、二次电池及电子装置,以改善硅基负极极片中电解液的润湿性不足的问题
[0035]本申请提供了一种负极极片、二次电池及电子装置,通过在含硅材料的负极材料层中添加陶瓷纳米纤维,陶瓷纳米纤维相互交织缠结形成浸润网络,使电解液在负极材料层内部孔隙有效填充并相互连通,提高负极极片中电解液的润湿性,为锂离子提供完整的传输通路,有利于降低二次电池中负极极片的析锂风险以及改善二次电池的容量衰减问题。另外,陶瓷纳米纤维本身也可以作为锂离子传输通道,使锂离子也能够沿陶瓷纳米纤维的晶格结构快速迁移,增加锂离子传输通路,进一步降低二次电池中负极极片的析锂风险以及改善二次电池的容量衰减问题。
Smart Images

Figure CN123017859A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of battery technology, and in particular to a negative electrode sheet, a secondary battery, and an electronic device. Background Technology
[0002] Silicon-based anodes are an effective strategy for improving the energy density of lithium-ion batteries, but the significant volume expansion they generate during cycling severely limits their practical application. One reason for this is that the expansion of silicon-containing materials pushes aside surrounding particles, increasing porosity around the silicon particles. Simultaneously, as cycling progresses, the electrolyte is gradually consumed and reduced, becoming insufficient to completely fill the pores inside the electrode, especially around the silicon particles. In this situation, due to insufficient electrolyte wettability, cavities easily form in the electrode, hindering the effective transport of lithium ions. This not only increases the risk of lithium plating on the anode but may also lead to accelerated capacity decay of the lithium-ion battery, becoming a key factor limiting performance.
[0003] Therefore, how to effectively improve the wettability of electrolyte in silicon-based anode sheets has become an important challenge that urgently needs to be addressed in current lithium-ion battery manufacturing technology. Summary of the Invention
[0004] The purpose of this application is to provide a negative electrode, a secondary battery, and an electronic device to improve the problem of insufficient wettability of the electrolyte in a silicon-based negative electrode.
[0005] In a first aspect, this application provides a negative electrode sheet, which includes a negative current collector and a negative electrode material layer formed on at least one surface of the negative current collector, the negative electrode material layer including silicon-containing material and ceramic nanofibers.
[0006] In the above technical solution, by adding ceramic nanofibers to the silicon-containing negative electrode material layer, the ceramic nanofibers intertwine and entangle to form a wetting network, which improves the wettability of the electrolyte in the negative electrode sheet, which is beneficial to reduce the risk of lithium plating in the negative electrode sheet of the secondary battery and improve the capacity decay problem of the secondary battery.
[0007] In one possible implementation, the mass percentage of ceramic nanofibers is 0.5% to 10%, depending on the mass of the negative electrode material layer.
[0008] In the above technical solution, by controlling the mass percentage content of ceramic nanofibers within the above range, the ceramic nanofibers can form an interconnected wetting network without increasing excessive ineffective space in the negative electrode. This reduces the risk of lithium plating in the negative electrode of the secondary battery and improves the capacity decay problem of the secondary battery, while also contributing to the improvement of the volumetric energy density of the secondary battery.
[0009] In one possible implementation, the negative electrode material layer is a single-layer coating, and the mass percentage of ceramic nanofibers is W1, which is 1% to 10% based on the mass of the negative electrode material layer.
[0010] In the above technical solution, when the negative electrode material layer is a single-layer coating, by adjusting W1 within the above range, the wetting network formed by ceramic nanofibers allows the electrolyte to fully wet and spread inside the negative electrode material layer, accelerating the transport rate of lithium ions in the negative electrode material layer. This is beneficial to further reduce the risk of lithium plating on the negative electrode sheet and improve the capacity decay problem of the secondary battery.
[0011] In one possible implementation, the mass percentage of silicon in the negative electrode material layer is W2, where 0.06 ≤ W1 / W2 ≤ 0.8.
[0012] In the above technical solution, when the negative electrode material layer is a single-layer coating, the W1 / W2 ratio is adjusted within the above range to match the amount of ceramic nanofibers added with the silicon content in the negative electrode material layer. This allows for the formation of a suitable wetting network structure within the pore volume generated by the volume expansion of the silicon-containing material. This not only helps reduce the risk of lithium plating on the negative electrode sheet and improve the capacity decay problem of the secondary battery, but also helps to increase the volumetric energy density of the secondary battery.
[0013] In one possible implementation, the negative electrode material layer includes a first negative electrode material layer and a second negative electrode material layer. Along the thickness direction of the negative electrode sheet, the first negative electrode material layer is disposed between the negative electrode current collector and the second negative electrode material layer. The second negative electrode material layer includes silicon-containing materials and ceramic nanofibers. Based on the total mass of the first and second negative electrode material layers, the mass percentage of ceramic nanofibers in the second negative electrode material layer is W3, where W3 is 0.5% to 8%.
[0014] In the above technical solution, when the negative electrode material layer is a multilayer coating and the second negative electrode material layer includes silicon-containing materials, by adding ceramic nanofibers to the second negative electrode material layer and adjusting W3 within the above range, the ceramic nanofibers form an interconnected wetting network in the second negative electrode material layer. In this way, with the increase of porosity in the second negative electrode material layer, the electrolyte can form a continuous electrolyte liquid phase layer along the wetting network, providing a complete transport path for lithium ions. This is beneficial to further reduce the risk of lithium plating on the negative electrode sheet and improve the problem of rapid capacity decay of secondary batteries.
[0015] In one possible implementation, based on the total mass of the first and second anode material layers, the mass percentage of silicon in the second anode material layer is W4, where 0.02 ≤ W3 / W4 ≤ 0.5.
[0016] In the above technical solution, by adjusting W3 / W4 within the aforementioned range, the amount of ceramic nanofibers added is matched with the silicon content in the second negative electrode material layer. This allows for the formation of a suitable wetting network structure within the pore volume generated by the volume expansion of the silicon-containing material. This prevents the electrolyte from having difficulty entering the pores due to occupying too many pores in the second negative electrode material layer, thus affecting the transport of lithium ions. This is beneficial for further reducing the risk of lithium plating on the negative electrode sheet and improving the problem of rapid capacity decay in secondary batteries.
[0017] In one possible implementation, the negative electrode active material in the first negative electrode material layer includes one or more of graphite, hard carbon, and lithium titanate; the negative electrode active material in the second negative electrode material layer includes one or more of silicon-carbon composite material, silicon-oxygen composite material, micron-sized silicon, and nano-sized silicon; or, the negative electrode active material in the second negative electrode material layer includes one or more of silicon-carbon composite material, silicon-oxygen composite material, micron-sized silicon, and nano-sized silicon, as well as one or more of graphite, hard carbon, and lithium titanate.
[0018] In the above technical solutions, the use of silicon-containing materials is beneficial to improving the volumetric energy density of the secondary battery, while the use of carbon-containing materials is beneficial to improving the stability of the secondary battery.
[0019] In one possible implementation, the negative electrode active material in the negative electrode material layer includes one or more of silicon-carbon composite materials, silicon-oxygen composite materials, micron-sized silicon, and nano-sized silicon; or, the negative electrode active material in the negative electrode material layer includes one or more of silicon-carbon composite materials, silicon-oxygen composite materials, micron-sized silicon, and nano-sized silicon, as well as one or more of graphite, hard carbon, and lithium titanate.
[0020] In the above technical solutions, the use of silicon-containing materials is beneficial to improving the volumetric energy density of the secondary battery, while the use of carbon-containing materials is beneficial to improving the stability of the secondary battery.
[0021] In one possible implementation, the ceramic nanofibers satisfy at least one of the following:
[0022] (1) The length of the ceramic nanofibers is 5–30 μm;
[0023] (2) The diameter of the ceramic nanofibers is 50-300 nm;
[0024] (3) The specific surface area of ceramic nanofibers is 100–1000 m². 2 / g; or
[0025] (4) The lithium-ion conductivity of ceramic nanofibers is greater than or equal to 3 × 10⁻⁶. -8 S / cm.
[0026] In the above technical solution, controlling the length of ceramic nanofibers within the above range is beneficial to promoting the interweaving and entanglement of ceramic nanofibers to form an impregnation network, and it is not easy to cause particle agglomeration and slurry clumping due to excessive entanglement and bending, thereby affecting the uniformity and consistency of the appearance of the negative electrode coating.
[0027] By controlling the diameter of ceramic nanofibers within the aforementioned range, they are less prone to breakage and fragmentation, and the excessive ineffective space within the negative electrode is avoided. This facilitates the interweaving and entanglement of ceramic nanofibers to form a wetting network, and also contributes to improving the volumetric energy density of the secondary battery.
[0028] Regulating the specific surface area of ceramic nanofibers within the above range is beneficial to improving the wettability of the electrolyte in the negative electrode sheet while reducing the side reaction sites between the electrolyte and the material inside the negative electrode sheet, thereby better balancing the wettability of the electrolyte in the negative electrode sheet and the cycle performance of the secondary battery.
[0029] Select lithium-ion batteries with a conductivity greater than or equal to 3 × 10⁻⁶. -8 Ceramic nanofibers with a conductivity of S / cm, or those capable of spontaneously generating lithium ions during secondary battery charging with a conductivity greater than or equal to 3×10⁻⁶. -8 Ceramic nanofibers with a density of S / cm allow lithium ions to migrate rapidly along the lattice structure of the ceramic nanofibers during the charging and discharging process of the secondary battery. The ceramic nanofibers themselves serve as lithium ion transport channels, maintaining the integrity of the lithium ion transport pathway. This helps reduce the risk of lithium plating on the negative electrode in the secondary battery and improves the capacity decay problem of the secondary battery.
[0030] In one possible implementation, the ceramic nanofibers are selected from at least one of the following: alumina nanofibers, titanium dioxide nanofibers, zinc oxide nanofibers, vanadium oxide nanofibers, molybdenum oxide nanofibers, zirconium oxide nanofibers, aluminum hydroxide nanofibers, silicon carbide nanofibers, boron nitride nanofibers, lithium lanthanum zirconium oxide nanofibers, lithium lanthanum zirconium niobium oxide nanofibers, lithium lanthanum titanium oxide nanofibers, lithium titanium aluminum phosphate nanofibers, and lithium germanium aluminum phosphate nanofibers.
[0031] In the above technical solution, the ceramic nanofibers themselves have good wettability to the electrolyte. In addition, the ceramic nanofibers themselves have high lithium-ion conductivity or can form a substance with high lithium-ion conductivity during charging, which is beneficial to improving the lithium-ion transport capacity.
[0032] Secondly, this application provides a secondary battery that includes the negative electrode sheet in any of the solutions in the first aspect described above.
[0033] Thirdly, this application provides an electronic device that includes a secondary battery as described in any of the embodiments of the second aspect above.
[0034] The beneficial effects of this application are:
[0035] This application provides a negative electrode sheet, a secondary battery, and an electronic device. By adding ceramic nanofibers to a silicon-containing negative electrode material layer, the ceramic nanofibers intertwine and entangle to form a wetting network. This allows the electrolyte to effectively fill and interconnect the pores within the negative electrode material layer, improving the wettability of the electrolyte in the negative electrode sheet and providing a complete transport pathway for lithium ions. This helps reduce the risk of lithium plating on the negative electrode sheet in the secondary battery and improves the capacity decay problem. Furthermore, the ceramic nanofibers themselves can also serve as lithium ion transport channels, enabling lithium ions to migrate rapidly along the lattice structure of the ceramic nanofibers, increasing the lithium ion transport pathway and further reducing the risk of lithium plating on the negative electrode sheet in the secondary battery and improving the capacity decay problem. Attached Figure Description
[0036] One or more embodiments are illustrated by way of example with reference to the accompanying drawings, which are not intended to limit the embodiments, and elements having the same reference numerals in the drawings are designated as similar elements.
[0037] Figure 1 This is a schematic diagram of a portion of the internal structure of the negative electrode sheet in a related technology;
[0038] Figure 2 The images are scanning electron microscope (SEM) images of the negative electrode sheet of Embodiment 1-1 of this application at different magnifications.
[0039] Figure 3 The images are SEM images of the negative electrode sheet of Embodiment 2-1 of this application at different magnifications.
[0040] Explanation of reference numerals in the attached figures
[0041] 10 - Negative electrode active material particles, 20 - Cavity, 30 - Electrolyte. Detailed Implementation
[0042] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. All other embodiments obtained by those skilled in the art based on this application are within the scope of protection of this application.
[0043] The expansion of silicon-containing materials in silicon-based anodes causes particles inside the anode sheet to be squeezed and pushed apart, forming large pores around the active particles. Under these circumstances, the insufficient wettability of the electrolyte gradually becomes prominent, becoming a key factor restricting the performance of secondary batteries.
[0044] Figure 1 This is a schematic diagram of a portion of the internal structure of the negative electrode in a related technology. Figure 1 In the diagram, the elliptical structure represents the negative electrode active material particle 10, the white area formed between two negative electrode active material particles 10 represents the cavity 20, and the remaining part represents the electrolyte 30.
[0045] like Figure 1 As shown, negative electrode active material particles 10 are distributed in the negative electrode sheet, and multiple negative electrode active material particles 10 form a highly tortuous electrode structure in the negative electrode sheet. In this case, due to insufficient wettability of the electrolyte 30, the electrolyte 30 accumulates in the form of droplets in the pores between the negative electrode active material particles 10 (i.e., forming cavities 20) and cannot spread well. The formed cavities 20 cause the electrolyte 30 to be intermittent, thereby disrupting the connectivity of the lithium-ion transport path, causing some negative electrode active material particles 10 to lose lithium-ion transport channels. This not only increases the risk of lithium plating on the negative electrode sheet in the secondary battery, but may also cause a sharp capacity decay in the secondary battery.
[0046] Based on this, this application provides a negative electrode sheet to improve at least one of the problems of lithium plating on silicon-based negative electrodes caused by insufficient wettability of electrolyte and rapid capacity decay of secondary batteries.
[0047] The first aspect of this application provides a negative electrode sheet, which includes a negative current collector and a negative electrode material layer formed on at least one surface of the negative current collector. The negative electrode material layer includes a silicon-containing material and ceramic nanofibers. This application adds ceramic nanofibers to the silicon-containing negative electrode material layer. The ceramic nanofibers intertwine and entangle to form a wetting network, effectively filling and interconnecting the pores within the negative electrode material layer with electrolyte. This improves the wettability of the electrolyte in the negative electrode sheet, providing a complete transport pathway for lithium ions. This helps reduce the risk of lithium plating on the negative electrode sheet in secondary batteries and improves the capacity decay problem of secondary batteries. Furthermore, the ceramic nanofibers themselves can also serve as lithium ion transport channels, allowing lithium ions to migrate rapidly along the lattice structure of the ceramic nanofibers, increasing the lithium ion transport pathway and further reducing the risk of lithium plating on the negative electrode sheet in secondary batteries and improving the capacity decay problem of secondary batteries.
[0048] In this application, the silicon-containing material in the negative electrode material layer is the negative electrode active material. This application does not impose any particular restrictions on the negative electrode active material in the negative electrode material layer, as long as it achieves the purpose of this application. For example, the negative electrode active material in the negative electrode material layer may only include silicon-containing materials. As another example, the negative electrode active material in the negative electrode material layer may also include other materials such as silicon-containing materials and carbon-containing materials.
[0049] In some embodiments of this application, the negative electrode active material in the negative electrode material layer may include one or more of silicon-carbon composite materials, silicon-oxygen composite materials, micron-sized silicon, and nano-sized silicon; or, the negative electrode active material in the negative electrode material layer may include one or more of silicon-carbon composite materials, silicon-oxygen composite materials, micron-sized silicon, and nano-sized silicon, as well as one or more of graphite, hard carbon, and lithium titanate.
[0050] As used in this application, based on the mass of the silicon-carbon composite material, the mass percentage content of silicon is 30% to 70%, and the mass percentage content of carbon is 30% to 70%. This application does not impose any particular limitation on the silicon-carbon composite material, as long as it achieves the purpose of this application. For example, the silicon-carbon composite material can be a composite material obtained by deposition. Exemplarily, the silicon-carbon composite material can be silicon material deposited on a carbon skeleton, or carbon material deposited on a silicon skeleton. Silicon-carbon composite materials, by combining silicon materials with carbon materials of different structures, significantly improve the capacity and electrochemical performance of the negative electrode material. They facilitate the insertion and extraction of large amounts of lithium ions during the charging and discharging process of electrochemical devices and can be used as a negative electrode material for secondary batteries. Silicon-oxygen composite materials include SiOx, where 0 < x < 2. Exemplarily, silicon-oxygen composite materials can include silicon suboxide (SiO, with a molar ratio of silicon to oxygen of 1:1) or SiO2. 1.2 (The molar ratio of silicon to oxygen is 1:1.2). Silicon-oxygen composite materials can be obtained by oxidizing silicon materials, thereby significantly improving the capacity and electrochemical performance of anode materials. They are beneficial for the insertion and extraction of large amounts of lithium ions during the charging and discharging process of electrochemical devices and can be used as anode materials for secondary batteries.
[0051] It should be noted that the aforementioned "negative electrode material layer formed on at least one surface of the negative electrode current collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode current collector along its own thickness direction, or it can be disposed on two surfaces of the negative electrode current collector along its own thickness direction. Here, "surface" can be the entire area of the negative electrode current collector or a part of the negative electrode current collector. This application has no particular limitation, as long as the purpose of this application can be achieved.
[0052] In some embodiments of this application, the mass percentage of ceramic nanofibers is 0.5% to 10% based on the mass of the negative electrode material layer. For example, the mass percentage of ceramic nanofibers can be 0.5%, 1%, 2%, 4%, 6%, 8%, 10%, or any combination of two of these values. Controlling the mass percentage of ceramic nanofibers within the above range is beneficial for the formation of a wetting network that interconnects the electrolyte, thereby reducing the risk of lithium plating on the negative electrode in the secondary battery and improving the capacity decay problem. It also contributes to the improvement of the volumetric energy density of the secondary battery. When the amount of ceramic nanofibers added is too low, insufficient ceramic nanofibers are insufficient to form a wetting network, making it difficult to exert a wetting effect, which is detrimental to reducing the risk of lithium plating on the negative electrode and improving the cycle performance of the secondary battery. When the amount of ceramic nanofibers added is too high, on the one hand, the excessive amount of ceramic nanofibers may occupy too much of the pores within the electrode, leading to a decrease in the porosity of the electrode and thus affecting the liquid absorption rate. This is also detrimental to reducing the risk of lithium plating on the negative electrode and improving the cycle performance of the secondary battery. On the other hand, excessive addition of ceramic nanofibers may result in insufficient addition of negative electrode active material in the negative electrode active material layer, which is not conducive to improving the volumetric energy density of the secondary battery.
[0053] In some embodiments of this application, the negative electrode material layer is a single-layer coating. Based on the mass of the negative electrode material layer, the mass percentage of ceramic nanofibers is W1, where W1 is 1% to 10%. For example, W1 can be 1%, 2%, 4%, 6%, 8%, 10%, or a range of any two of these values. When the negative electrode material layer is a single-layer coating and includes silicon-containing materials, due to the high expansion rate of silicon-containing materials, the porosity in the negative electrode material layer increases rapidly during the charging and discharging process of the secondary battery. The electrolyte is insufficient to completely fill the pores within the negative electrode material layer, resulting in the electrolyte failing to form a complete and continuous wetting network. Some silicon-containing material particles lose lithium-ion transport channels, leading to cleavage and rapid capacity decay in the secondary battery. This application regulates W1 within the aforementioned range, enabling ceramic nanofibers to form an interconnected wetting network in the negative electrode material layer. Since the negative electrode material layer is a single-layer coating, the pore growth inside the negative electrode material layer is relatively uniform during the charging and discharging process of the secondary battery. Therefore, the formed wetting network facilitates the full wetting and spreading of the electrolyte inside the negative electrode material layer, forming a complete lithium-ion transport channel network inside the negative electrode material layer. This accelerates the transport rate of lithium ions in the pores of the negative electrode material layer, further reducing the risk of lithium plating on the negative electrode sheet in the secondary battery and the risk of rapid capacity decay of the secondary battery.
[0054] In some embodiments of this application, when the negative electrode material layer is a single-layer coating, the mass percentage of silicon in the negative electrode material layer is W2, where 0.06 ≤ W1 / W2 ≤ 0.8. For example, W1 / W2 can be 0.06, 0.1, 0.3, 0.5, 0.6, 0.8, or a range of any two of these values. When the negative electrode material layer is a single-layer coating, adjusting W1 / W2 within the above range allows the amount of ceramic nanofibers added to match the silicon content in the negative electrode material layer, thereby forming a suitable wetting network structure in the negative electrode material layer. This is more conducive to reducing the risk of lithium plating on the negative electrode sheet in the secondary battery. When W1 / W2 < 0.06, compared to the pore volume generated by the volume expansion of the silicon-containing material, the amount of ceramic nanofibers added is too small to form an interconnected wetting network within the relatively large pore volume, making it difficult to promote lithium-ion transport and thus not conducive to reducing the risk of lithium plating on the negative electrode sheet in the secondary battery. When W1 / W2 > 0.8, the content of silicon-containing materials in the negative electrode material layer is relatively low, which is not conducive to improving the volumetric energy density of the secondary battery.
[0055] It is understood that in some embodiments of this application, 10% ≤ W2 ≤ 60%, and adjusting W2 within the above-mentioned range is beneficial to obtaining a secondary battery with high energy density and high stability.
[0056] In some embodiments of this application, the negative electrode material layer includes a first negative electrode material layer and a second negative electrode material layer. Along the thickness direction of the negative electrode sheet, the first negative electrode material layer is disposed between the negative electrode current collector and the second negative electrode material layer. The second negative electrode material layer includes silicon-containing material and ceramic nanofibers. Based on the total mass of the first and second negative electrode material layers, the mass percentage of ceramic nanofibers in the second negative electrode material layer is W3, where W3 is 0.5% to 8%. For example, W3 can be 0.5%, 1%, 2%, 4%, 6%, 8%, or a range consisting of any two of these values. In cases where the negative electrode material layer is a multilayer coating and the second negative electrode material layer includes silicon-containing materials, the high expansion rate of the silicon-containing materials leads to a rapid increase in porosity during the charging and discharging process of the secondary battery. The electrolyte is insufficient to completely fill the pores within the second negative electrode material layer, and the poor wettability between the silicon-containing material particles and the electrolyte causes the electrolyte to accumulate in droplets at the pores, preventing proper spreading. This results in the electrolyte failing to form a complete and continuous wetting network, and some silicon-containing material particles losing their lithium-ion transport channels. Consequently, the risk of precipitation in the negative electrode sheet of the secondary battery is high, and the secondary battery is prone to rapid capacity decay. This application addresses this issue by adding ceramic nanofibers to the second negative electrode material layer and controlling W3 within the aforementioned range. This allows the ceramic nanofibers to form an interconnected wetting network in the second negative electrode material layer. Thus, even with increased porosity in the second negative electrode material layer, a continuous electrolyte liquid phase layer can still be formed along the ceramic nanofibers, maintaining the integrity of the lithium-ion transport pathway. This helps reduce the risk of precipitation in the negative electrode sheet and improves the problem of rapid capacity decay in the secondary battery.
[0057] In some embodiments of this application, when the negative electrode material layer is a multilayer coating and the second negative electrode material layer includes silicon-containing materials, the mass percentage of silicon in the second negative electrode material layer is W4, based on the total mass of the first and second negative electrode material layers, and 0.02 ≤ W3 / W4 ≤ 0.5. For example, W3 / W4 can be 0.02, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, or a range of any two of these values. When the negative electrode material layer is a multilayer coating and the second negative electrode material layer includes silicon-containing materials, controlling W3 / W4 within the above range ensures that the amount of ceramic nanofibers added matches the silicon content in the second negative electrode material layer, thereby forming a suitable wetting network structure in the second negative electrode material layer. This helps reduce the risk of chemical degradation of the negative electrode sheet and improves the problem of rapid capacity decay in the secondary battery. When W3 / W4 < 0.02, the amount of ceramic nanofibers added is too small compared to the pore volume generated by the volume expansion of the silicon-containing material in the second negative electrode layer. This insufficient addition is inadequate to form an interconnected wetting network within the relatively large pore volume, hindering its role in promoting lithium-ion transport and failing to mitigate the chelation risk of the negative electrode and the rapid capacity decay of the secondary battery. When W3 / W4 > 0.5, the amount of ceramic nanofibers added is excessive compared to the pore volume generated by the volume expansion of the silicon-containing material in the second negative electrode layer. Excessive ceramic nanofibers occupy too many pores in the second negative electrode layer, making it difficult for the electrolyte to enter the pores. This, in turn, hinders lithium-ion transport and is detrimental to mitigating the chelation risk of the negative electrode and the rapid capacity decay of the secondary battery.
[0058] In some embodiments of this application, 8% ≤ W4 ≤ 50%, and adjusting W4 within the above-mentioned range is beneficial to obtaining a secondary battery with high energy density and high stability.
[0059] In some embodiments of this application, W4 can be controlled within the above range by: controlling the ratio of each negative electrode active material and ceramic nanofiber in the second negative electrode material layer; and / or, controlling the coating quality CW1 of the first negative electrode material layer and the coating quality CW2 of the second negative electrode material layer.
[0060] In some embodiments of this application, 25% ≤ CW2 / (CW1+CW2) ≤ 80%. By adjusting CW2 / (CW1+CW2) within the above range, W4 satisfies 8% ≤ W4 ≤ 50%. When CW2 / (CW1+CW2) is too low, the content of silicon material in the negative electrode is low, affecting the volumetric energy density of the secondary battery. When CW2 / (CW1+CW2) is too high, the content of silicon material in the second negative electrode material layer is excessive. During the charging and discharging process of the secondary battery, the expansion rate of the silicon material in the second negative electrode material layer is high, and the porosity increases rapidly. The electrolyte is difficult to completely fill the pores in the second negative electrode material layer, which is not conducive to improving the cycle performance of the secondary battery.
[0061] It should be noted that this application does not impose any particular restrictions on the negative electrode active materials in the first and second negative electrode material layers, as long as the purpose of this application can be achieved. For example, the negative electrode active material in the first negative electrode material layer may include silicon-containing materials or may not include silicon-containing materials; the negative electrode active material in the second negative electrode material layer may include only silicon-containing materials, or the negative electrode active material in the second negative electrode material layer may include silicon-containing materials and other materials such as carbon-containing materials.
[0062] It is understood that, based on the total mass of the first and second negative electrode material layers, the mass percentage of silicon in the first negative electrode material layer is W5, where 0% ≤ W5 ≤ 2%. When W5 is within the above range, it is beneficial to construct a negative electrode sheet with a gradient porosity structure, reducing the risk of cleavage in the negative electrode sheet. Furthermore, when W5 = 0%, it is beneficial not only to construct an electrode sheet with a gradient porosity structure, reducing the risk of cleavage in the negative electrode sheet, but also to improve the problem of increased porosity in the first negative electrode material layer caused by the volume expansion of silicon-containing materials during the charging and discharging process of the secondary battery. In some embodiments of this application, the negative electrode active material in the first negative electrode material layer may include one or more of graphite, hard carbon, and lithium titanate; the negative electrode active material in the second negative electrode material layer may include one or more of silicon-carbon composite materials, silicon-oxygen composite materials, micron-sized silicon, and nano-sized silicon; or, the negative electrode active material in the second negative electrode material layer may include one or more of silicon-carbon composite materials, silicon-oxygen composite materials, micron-sized silicon, and nano-sized silicon, as well as one or more of graphite, hard carbon, and lithium titanate. Using silicon-containing materials is beneficial for improving the capacity of secondary batteries, while using carbon-containing materials is beneficial for improving the stability of secondary batteries.
[0063] It should also be noted that the first negative electrode material layer of this application may or may not contain ceramic nanofibers, and this application does not have any particular restrictions on this.
[0064] In some embodiments of this application, the ceramic nanofibers satisfy at least one of the following:
[0065] (1) The length of the ceramic nanofibers is 5–30 μm;
[0066] (2) The diameter of the ceramic nanofibers is 50-300 nm;
[0067] (3) The specific surface area of ceramic nanofibers is 100–1000 m². 2 / g; or
[0068] (4) The lithium-ion conductivity of ceramic nanofibers is greater than or equal to 3 × 10⁻⁶. -8 S / cm.
[0069] The length of the ceramic nanofibers can be 5μm, 10μm, 15μm, 20μm, 30μm, or any combination of two of these values. Controlling the length of the ceramic nanofibers within this range promotes their interweaving and entanglement to form a wetting network. When the length of the ceramic nanofibers is too short, they are difficult to connect fully, hindering the formation of a complete wetting network; when the length of the ceramic nanofibers is too long, excessive entanglement and bending can lead to particle agglomeration and slurry clumping, thus affecting the uniformity and consistency of the coating appearance.
[0070] The diameter of ceramic nanofibers can be 50 nm, 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, or any combination of two of these values. Controlling the diameter of the ceramic nanofibers within this range prevents them from easily breaking during processes such as stirring or calendering, thus facilitating their interweaving and formation of a wetting network. If the diameter of the ceramic nanofibers is too small, their mechanical strength is insufficient, making them prone to breakage during stirring or calendering, which is detrimental to their interweaving and network formation. Furthermore, a small diameter reduces the lithium-ion conductivity of the nanofibers themselves, hindering lithium-ion transport. Conversely, an excessively large diameter increases the ineffective space within the negative electrode, negatively impacting the energy density of the secondary battery.
[0071] The length-to-diameter ratio (hereinafter referred to as aspect ratio) of ceramic nanofibers can range from 50 to 200. For example, the aspect ratio of ceramic nanofibers can be 50, 100, 200, or any combination of two of these values. Controlling the aspect ratio of ceramic nanofibers within this range is beneficial for promoting the interweaving and entanglement of ceramic nanofibers to form a wetting network, improving the uniformity and consistency of the coating appearance, and also enhancing the volumetric energy density of the secondary battery.
[0072] The specific surface area of ceramic nanofibers can reach 100 m². 2 / g、200m 2 / g、300m 2 / g、400m 2 / g、500m 2 / g、600m 2 / g、800m 2 / g, 1000m 2 / g or a range consisting of any two of these values. Regulating the specific surface area of ceramic nanofibers within this range is beneficial for improving the electrolyte wettability of the negative electrode while reducing side reaction sites between the electrolyte and the materials within the negative electrode, thus better balancing the electrolyte wettability and side reactions of the negative electrode. When the specific surface area of ceramic nanofibers is too low, it means that the surface of the ceramic nanofibers is relatively smooth, resulting in a poor effect on improving the electrolyte wettability. When the specific surface area of ceramic nanofibers is too high, the number of side reaction sites between the electrolyte and the materials within the negative electrode increases, leading to a decrease in the initial coulombic efficiency of the secondary battery; in addition, when the specific surface area of ceramic nanofibers is too high, electrolyte consumption accelerates during charge and discharge, which is detrimental to improving cycle performance.
[0073] The length and diameter of ceramic nanofibers have different effects on their specific surface area. The diameter has a greater impact on the specific surface area, while the length has a smaller, usually negligible, effect. The diameter of ceramic nanofibers is inversely proportional to their specific surface area; the smaller the diameter, the larger the specific surface area. For example, the specific surface area of a 20 nm diameter ceramic nanofiber is much larger than that of a 150 nm diameter ceramic nanofiber.
[0074] In other words, when the diameter of ceramic nanofibers is too small, not only is their mechanical strength insufficient and they are prone to breakage during processes such as stirring or calendering, but it may also affect the specific surface area of the ceramic nanofibers to be too large, leading to an increase in the side reaction sites between the electrolyte and the negative electrode material, a decrease in the initial coulombic efficiency of the secondary battery, and accelerated electrolyte consumption during charging and discharging, which is not conducive to improving cycle performance.
[0075] The lithium-ion conductivity of ceramic nanofibers can be categorized into two scenarios: First, the ceramic nanofibers themselves possess lithium-ion conductivity. Second, the ceramic nanofibers themselves do not possess lithium-ion conductivity, but during secondary battery charging, they can spontaneously react to generate a substance with lithium-ion conductivity. For example, alumina ceramic nanofibers themselves do not possess lithium-ion conductivity; however, during secondary battery charging, they can spontaneously react to generate lithium aluminate, which possesses lithium-ion conductivity (this process is spontaneous and requires no additional conditions).
[0076] For the first situation mentioned above, this application can select materials that inherently possess lithium-ion conductivity and have a lithium-ion conductivity greater than or equal to 3 × 10⁻⁶. -8Ceramic nanofibers with a conductivity of S / cm can be selected. For the second scenario mentioned above, those that do not inherently possess lithium-ion conductivity but can spontaneously generate lithium ions during secondary battery charging, exhibiting a conductivity greater than or equal to 3 × 10⁻⁶. -8 Ceramic nanofibers with a density of S / cm. In this way, during the charging and discharging process of a secondary battery, lithium ions can migrate rapidly along the lattice structure of the ceramic nanofibers, using the ceramic nanofibers themselves as lithium ion transport channels. This maintains the integrity of the lithium ion transport pathway, which helps reduce the risk of lithium plating on the negative electrode in the secondary battery and improves the capacity decay problem.
[0077] It should be noted that the higher the lithium-ion conductivity of ceramic nanofibers, the better; however, due to current material limitations, the lithium-ion conductivity of ceramic nanofibers can currently reach 3 × 10⁻⁶. -8 S / cm~1×10 -1 S / cm. Similarly, ceramic nanofibers can spontaneously react to generate lithium ions during charging, with a conductivity of 3×10⁻⁶. -8 S / cm~1×10 -1 Materials with a conductivity of S / cm. For example, lithium-ion conductivity can be 3 × 10⁻⁶. -8 S / cm, 5.4×10 -4 S / cm, 3.6×10 -8 S / cm, 6.4×10 -7 S / cm, 4.7×10 - 6 S / cm, 2.7×10 -4 S / cm, 1×10 -1 S / cm can be any two of these values within a range. Adjusting the lithium-ion conductivity of ceramic nanofibers within this range facilitates the rapid migration of lithium ions along the crystal structure of the ceramic nanofibers, allowing the ceramic nanofibers themselves to act as lithium-ion transport channels. This maintains the integrity of the lithium-ion transport pathway, which helps reduce the risk of lithium plating on the negative electrode in secondary batteries and improves the capacity decay problem.
[0078] It is understandable that the length, diameter, specific surface area, and lithium-ion conductivity of ceramic nanofibers can be adjusted in any way that meets the purpose of this application. For example, ceramic nanofibers with different lengths, diameters, specific surface areas, and lithium-ion conductivity can be obtained by purchasing them. For instance, ceramic nanofibers with different lengths, diameters, specific surface areas, and lithium-ion conductivity can be prepared using electrospinning technology. During the preparation process, the length of ceramic nanofibers can be adjusted individually by modifying spinning process parameters such as the pH value and concentration of the precursor solution, the properties of the catalyst, and the spinning voltage, or by methods such as crushing and sieving. The diameter of ceramic nanofibers can also be adjusted individually by modifying spinning process parameters such as the pH value, the concentration of the precursor solution, the properties of the catalyst, and the spinning voltage. The specific surface area of ceramic nanofibers can be adjusted individually by modifying calcination parameters and spinning rate. When ceramic nanofibers themselves have lithium-ion conductivity, the lithium-ion conductivity of ceramic nanofibers can be adjusted individually by modifying doping and sintering processes. When ceramic nanofibers can spontaneously react to generate substances with lithium-ion conductivity, the structural composition of ceramic nanofibers can be adjusted individually by modifying doping and sintering processes, thereby regulating the lithium-ion conductivity of the ceramic nanofiber products generated by the spontaneous reaction.
[0079] This application does not impose any particular limitation on the type of ceramic nanofibers, as long as they can achieve the purpose of this application. For example, the ceramic nanofibers can be selected from at least one of the following: alumina nanofibers, titanium oxide nanofibers, zinc oxide nanofibers, vanadium oxide nanofibers, molybdenum oxide nanofibers, zirconium oxide nanofibers, aluminum hydroxide nanofibers, silicon carbide nanofibers, lithium lanthanum zirconium oxide nanofibers, lithium lanthanum zirconium niobium oxide nanofibers, lithium lanthanum titanium oxide nanofibers, lithium aluminum titanium phosphate nanofibers, and lithium aluminum germanium phosphate nanofibers. Among these, alumina nanofibers, titanium oxide nanofibers, zinc oxide nanofibers, vanadium oxide nanofibers, molybdenum oxide nanofibers, zirconium oxide nanofibers, aluminum hydroxide nanofibers, and silicon carbide nanofibers can form a material with high lithium-ion conductivity during charging, while lithium lanthanum zirconium oxide nanofibers, lithium lanthanum zirconium niobium oxide nanofibers, lithium lanthanum titanium oxide nanofibers, lithium aluminum titanium phosphate nanofibers, and lithium aluminum germanium phosphate nanofibers themselves have high lithium-ion conductivity. The aforementioned ceramic nanofibers exhibit good wettability to electrolytes. Furthermore, these ceramic nanofibers possess high lithium-ion conductivity or can form substances with high lithium-ion conductivity during charging, thereby enhancing lithium-ion transport capabilities.
[0080] The negative electrode sheet of this application may further include a conductive agent and a binder. This application does not impose any particular limitations on the conductive agent and binder in the negative electrode sheet. For example, the conductive agent may be selected from at least one of carbon nanotubes, conductive carbon black, carbon nanofibers, conductive graphene, and sheet-like conductive graphite. The binder may be selected from at least one of polyvinylidene fluoride (PVDF), carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyacrylic acid (PAA), polyvinyl alcohol (PVA), and polyurethane (PU).
[0081] This application does not impose any particular limitations on the thickness and material of the negative electrode current collector, as long as it achieves the purpose of this application. For example, the thickness of the negative electrode current collector is 5 μm to 20 μm, preferably 6 μm to 18 μm, and more preferably 8 μm to 12 μm. The material may include copper foil, copper alloy foil, or composite current collector, etc.
[0082] A second aspect of this application provides a secondary battery comprising the negative electrode, positive electrode, electrolyte, and separator provided in the first aspect. The separator is disposed between the negative electrode and the positive electrode. Because the ceramic nanofibers added to the negative electrode material layer intertwine and form a wetting network, the electrolyte effectively fills and interconnects the pores within the silicon-containing negative electrode material layer. Furthermore, the ceramic nanofibers themselves can also serve as lithium-ion transport channels, maintaining the integrity of the lithium-ion transport pathway, which helps reduce the risk of lithium plating on the negative electrode in the secondary battery and improves the problem of rapid capacity decay in the secondary battery.
[0083] It should be noted that, in the specific embodiments of this application, lithium-ion batteries are used as an example of secondary batteries to explain this application. However, the secondary batteries in this application are not limited to lithium-ion batteries, and can include any device in which an electrochemical reaction occurs. For example, the secondary batteries in this application may include, but are not limited to: lithium metal secondary batteries, lithium-ion secondary batteries (lithium-ion batteries), lithium polymer secondary batteries, or lithium-ion polymer secondary batteries (lithium-ion polymer batteries), etc.
[0084] The secondary battery of this application will be described in detail below.
[0085] The electrolyte can be any known electrolyte. The electrolyte may include organic solvents, lithium electrolyte salts, and additives. This application does not impose specific limitations on its type; it can be selected according to actual needs.
[0086] For example, the organic solvent in the electrolyte can be one or more of the following: ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butenyl carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).
[0087] The electrolyte lithium salt can be one or more of the following: LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bisfluorosulfonylimide), LiTFSI (lithium bistrifluoromethanesulfonylimide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalate borate), LiBOB (lithium dioxalate borate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorodioxalate phosphate), and LiTFOP (lithium tetrafluorooxalate phosphate).
[0088] The additives in the electrolyte may be one or more of the following: vinylene carbonate (VC), ethylene ethylene carbonate (VEC), succinate (SN), adiponitrile (AND), 1,3-propenesulfonate lactone (PST), sulfonate cyclic quaternary ammonium salts, tris(trimethylsilane) phosphate (TMSP) and tris(trimethylsilane) borate (TMSB).
[0089] The electrolyte described above can be prepared according to conventional methods in the art. It can be prepared by uniformly mixing an organic solvent, a lithium electrolyte salt, and other optional additives. There are no particular restrictions on the order in which the materials are added. For example, the lithium electrolyte salt and other optional additives can be added to an organic solvent and mixed uniformly to obtain the electrolyte. Alternatively, the lithium electrolyte salt can be added to the organic solvent first, and then the other optional additives can be added to the organic solvent separately or simultaneously.
[0090] diaphragm
[0091] A separator is used to separate the positive and negative electrodes, preventing internal short circuits in the secondary battery, allowing electrolyte ions to pass freely, and not affecting the electrochemical charging and discharging process. This application does not impose any particular limitation on the separator, as long as it achieves the purpose of this application. For example, the separator material may include, but is not limited to, at least one of polyethylene (PE), polyolefins (PO) primarily composed of polypropylene (PP), polyester (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex, or aramid; the separator type may include at least one of woven membrane, nonwoven membrane, microporous membrane, composite membrane, rolled membrane, or spun membrane.
[0092] In this application, the diaphragm may include a substrate and a surface treatment layer. The substrate may be a nonwoven fabric or composite membrane with a porous structure, and the material of the substrate may include at least one of polyethylene, polypropylene, polyethylene terephthalate, or polyimide. Optionally, a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric, or a polypropylene-polyethylene-polypropylene porous composite membrane may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing polymers and inorganic materials. For example, the inorganic layer includes inorganic particles and an adhesive. This application does not have any particular limitation on the aforementioned inorganic particles, and may include at least one of alumina, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, or barium sulfate. This application does not have any particular limitation on the aforementioned adhesives, and may include at least one of the aforementioned adhesives. The polymer layer contains a polymer, the polymer material of which includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride, or poly(vinylidene fluoride-hexafluoropropylene).
[0093] The secondary battery of this application also includes a packaging bag for containing the positive electrode, negative electrode, separator, and electrolyte, as well as other components known in the art for secondary batteries. This application does not limit the aforementioned other components. This application does not impose any particular limitation on the packaging bag; it can be any packaging bag known in the art, as long as it can achieve the purpose of this application.
[0094] The preparation process of the secondary battery described in this application is well known to those skilled in the art, and this application has no particular limitations. For example, it may include, but is not limited to, the following steps: stacking the positive electrode, separator, and negative electrode in sequence, and performing operations such as winding and folding as needed to obtain a wound electrode assembly; placing the electrode assembly in a packaging bag; injecting electrolyte into the packaging bag and sealing it to obtain a secondary battery; or stacking the positive electrode, separator, and negative electrode in sequence, and then fixing the four corners of the entire stacked structure with tape to obtain a stacked electrode assembly; placing the electrode assembly in a packaging bag; injecting electrolyte into the packaging bag and sealing it to obtain a secondary battery. In addition, overcurrent protection components, conductive plates, etc., may be placed in the packaging bag as needed to prevent the internal pressure of the secondary battery from rising and overcharging / discharging.
[0095] A third aspect of this application provides an electronic device that includes the secondary battery found in any of the foregoing embodiments. Therefore, the electronic device provided by this application has good performance.
[0096] This application does not specifically limit the type of electronic device, which can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, laptops, pen input computers, mobile computers, e-book players, portable telephones, portable fax machines, portable copiers, portable printers, stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini CDs, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, backup power supplies, motors, automobiles, motorcycles, electric bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries, and lithium-ion capacitors, etc.
[0097] Example
[0098] The embodiments and comparative examples provided below illustrate the implementation of this application in more detail. Various tests and evaluations were conducted according to the methods described below. Furthermore, unless otherwise specified, "parts" and "%" are quality standards.
[0099] Test methods and equipment:
[0100] Obtaining the film:
[0101] The secondary battery was discharged at a constant current of 0.5C to the discharge cutoff voltage at 25±3℃. The secondary battery was then disassembled under an argon atmosphere, and the negative electrode sheet was soaked in dimethyl carbonate solvent for 2 hours and dried at 60℃ for 1 hour to obtain the negative electrode sheet. The discharge cutoff voltage of the secondary battery in the embodiments and comparative examples of this application is 3.0V. It is understood that when the voltage range marked on the battery packaging is 3.0V to 4.45V, the charging cutoff voltage is 4.45V and the discharging cutoff voltage is 3.0V. Unless otherwise specified, the charging cutoff voltage of the example secondary battery is 4.45V and the discharging cutoff voltage is 3.0V.
[0102] Obtaining ceramic nanofibers:
[0103] The disassembled negative electrode sheet was soaked in water for 1 hour to loosen the negative electrode material layer. The negative electrode material layer was then scraped off and repeatedly washed and filtered three times with excess water. The filtered powder was placed in a vacuum oven and dried at 60°C for 12 hours. A glass bottle was filled with 2 / 3 ester electrolyte, and the powder was placed on the surface of the electrolyte and allowed to stand for 10 minutes. Because the density of ceramic nanofibers is higher than that of graphite, silicon-containing materials, and the conductive agents and binders in the negative electrode material layer, and because ceramic nanofibers have significantly improved wetting ability with the electrolyte compared to graphite, silicon-containing materials, and the conductive agents and binders in the negative electrode material layer, ceramic nanofibers will sink to the bottom more easily. The above steps were repeated multiple times until only ceramic nanofibers remained in the bottom layer, thus obtaining ceramic nanofibers.
[0104] Unless otherwise specified, the following test methods shall be performed using the electrode sheets or ceramic nanofibers obtained in the above manner.
[0105] Methods for testing the length and diameter of ceramic nanofibers:
[0106] The obtained ceramic nanofibers were added to anhydrous ethanol to prepare a ceramic nanofiber suspension with a concentration of 0.5 mg / mL. The ceramic nanofiber suspension was placed in an ultrasonic instrument and sonicated for 30 min to ensure uniform dispersion of the ceramic nanofibers. A small amount of the uniformly dispersed ceramic nanofiber suspension was drawn up using a capillary glass tube and drop-coated onto a smooth stainless steel foil surface, then allowed to air dry naturally. The dried ceramic nanofibers were observed under a scanning electron microscope. Five different observation areas were selected, and the length and diameter of at least 20 ceramic nanofibers in each area were measured. The average value of the measured length and diameter was taken as the length and diameter of the ceramic nanofiber.
[0107] Methods for testing the specific surface area of ceramic nanofibers:
[0108] The specific surface area of the obtained ceramic fiber material was measured using a Tristar II 3020M surface area analyzer via nitrogen adsorption. The specific testing was conducted according to the national standard GB / T19587-2017, "Determination of Specific Surface Area of Solid Substances by Gas Adsorption BET Method".
[0109] Methods for testing silicon content:
[0110] The electrode was obtained according to the method described in "Obtaining the Electrode". 0.2g of the electrode was placed in a nickel crucible, 1.5kg of KOH was added, and the mixture was heated at 400℃ for 45min. Then, it was soaked in 50ml of boiling water for 60min. The solution was then placed in a 100ml volumetric flask and diluted to volume. The solution was dissolved in nitric acid. A portion of the diluted solution was taken out and tested by inductively coupled plasma atomic emission spectrometry (ICP) to measure the silicon content in the electrode.
[0111] Test method for lithium-ion conductivity of ceramic nanofibers:
[0112] The obtained ceramic nanofibers were placed in a mold and rolled into circular sheets with a thickness of d. These sheets were then stacked in the order of stainless steel sheet / ceramic nanofiber sheet / stainless steel sheet (with the stainless steel having a radius of r, which is smaller than the radius of the solid electrolyte sheet) and assembled into a symmetrical battery in a suitably sized cell mold. The symmetrical battery was then subjected to AC impedance testing at 25±3℃ to obtain its impedance spectrum, with the test frequency range being 1×10⁻⁶. 5 The frequency range is Hz to 0.01Hz, and the perturbation voltage is 10mV. Then, the impedance spectrum obtained from the test is fitted with parameters using ZView software to obtain the lithium-ion transport resistance of the electrode. The above process is repeated three times, and the average value R1 of the three lithium-ion transport resistances is calculated. The lithium-ion conductivity of the ceramic nanofiber is σ = d / (R1 × πr). 2 ).
[0113] Test method for lithium-ion conductivity of secondary batteries:
[0114] Under conditions of 25±3℃, the secondary battery was adjusted to a 50% state of charge (SOC) through charge and discharge. Then, positive electrode discs, negative electrode discs, and separator discs with a diameter of 3 cm were cut from the positive electrode, negative electrode, and separator discs, respectively. These discs were stacked sequentially, placed in a suitably sized cell mold, and electrolyte was injected to assemble a symmetrical battery. The battery was then allowed to stand for 12 hours. Subsequently, AC impedance testing was performed on the symmetrical battery at 25±3℃ to obtain the impedance spectrum, with the test frequency range being 1×10⁻⁶. 5The frequency range is Hz to 0.01Hz, and the perturbation voltage is 10mV. Then, the impedance spectrum obtained from the test is fitted with parameters using ZView software to obtain the lithium-ion transport resistance of the secondary battery. The above process is repeated three times, and the average value R2 of the three lithium-ion transport resistances is calculated. This average value R2 is taken as the lithium-ion transport resistance of the secondary battery at 50% SOC.
[0115] Test method for the wetting ability of negative electrode sheet:
[0116] Cut the disassembled negative electrode sheet into square electrodes of a certain size and fix them with clamps. Prepare a high-precision electronic scale with an accuracy of less than 0.1 mg. Hang the cut square electrodes on the electronic scale using the clamps. After the scale reading stabilizes, zero the scale and immerse the bottom of the square electrodes in an electrolyte bath to a depth of 5 mm. Record the scale reading every 1 second until the reading stabilizes (fluctuation range ±0.1 mg), at which point the square electrode is considered saturated. The change in the scale reading represents the mass of electrolyte absorbed by the electrode. Let the cross-sectional area of the square electrode be A, the density of the electrolyte be ρ, and the mass of electrolyte absorbed by the square electrode in time t be Δm. Then, the electrode absorption rate is... The larger the P value, the faster the electrode absorbs liquid and the better its wetting ability.
[0117] Test method for the highest non-lithiation rate of negative electrode:
[0118] The secondary battery was subjected to charge-discharge cycles at a test temperature of 25±3℃. The cycle process was as follows: after the secondary battery was left to stand for 30 minutes, it was discharged at a constant current of 0.2C to the discharge cutoff voltage, and then left to stand for 30 minutes; it was then charged at a constant current of 0.5C to the charging cutoff voltage, and then charged at a constant voltage until it reached 0.05C (at which point it was fully charged). After 50 charge-discharge cycles of the secondary battery according to the above method, the fully charged secondary battery was disassembled to determine whether lithium plating occurred on the negative electrode. If metallic lithium appeared on the surface of the negative electrode, it was determined that lithium plating occurred on the negative electrode; otherwise, it was determined that no lithium plating occurred on the negative electrode.
[0119] If no lithium plating occurs on the negative electrode after 50 cycles, the same secondary battery is used, and the charging rate is increased by 0.1C each time while keeping other charging and discharging parameters unchanged. This cycle continues until lithium plating occurs on the negative electrode. The charging rate at which lithium plating does not occur on the negative electrode is defined as the highest non-lithiation rate for that secondary battery. The higher the highest non-lithiation rate, the less likely lithium plating will occur on the negative electrode of the secondary battery.
[0120] One method for determining whether the negative electrode has undergone lithium deposition is as follows: An image of the surface of the negative electrode facing the positive electrode is acquired, and an image recognition method is used to calculate the lithium deposition area of the lithium-deposited region on that surface, as well as the total area of the surface. The ratio of the lithium deposition area to the total area is taken as the lithium deposition area ratio. If the lithium deposition area ratio of the negative electrode is ≤0.5%, it is determined that lithium has not been deposited, and the next cycle of testing continues; if the lithium deposition area ratio of the negative electrode is greater than 0.5%, it is determined that lithium has been deposited, and the test for the highest non-deposition rate of the negative electrode ends.
[0121] Test methods for the cycle performance of secondary batteries:
[0122] The secondary battery was subjected to charge-discharge cycles at a test temperature of 25±3℃. The cycle process was as follows: charging at a constant current of 1C to the charging cutoff voltage, then charging at a constant voltage to 0.05C, and resting for 30 minutes. Then, discharging at a current of 0.5C to the discharging cutoff voltage, and resting for 30 minutes. The secondary battery was cycled according to the above method, and the discharge capacity of the nth cycle was recorded as C. n Using the discharge capacity of the second cycle as the 100% capacity baseline, the discharge capacity of the second cycle is recorded as C2. The capacity retention rate (%) of the nth cycle = C n / C2×100%. When the capacity retention rate of 5 consecutive cycles differs from the capacity retention rate of the previous cycle by ≥1%, it is considered that the secondary battery capacity has rapidly decayed, also known as cell drop. Record the cycle number k when the drop occurs. The later the cycle number of the drop occurs, the larger the value of k, and the better the cycle performance of the secondary battery.
[0123] Test method for volumetric energy density of secondary batteries:
[0124] At a test temperature of 25±3℃, the secondary battery was allowed to stand for at least 30 minutes, then charged at a constant current of 0.2C to the charging cutoff voltage, and then charged at a constant voltage to 0.05C. After standing for at least 30 minutes, it was discharged at a constant current of 0.2C to the discharge cutoff voltage, and the discharge energy E (in Wh) was measured. The length L, width W, and height H of the outer surface of the secondary battery were measured using a dimensional measuring instrument, and the volume V (in L) of the secondary battery was calculated, V = L × W × H. The volumetric energy density of the secondary battery, VED = E / V, is in Wh / L.
[0125] First set of examples and comparative examples: preparation of a secondary battery in which the negative electrode material layer in the negative electrode sheet has a double-layer structure.
[0126] Example 1-1
[0127] <Preparation of Negative Electrode Sheets>
[0128] Graphite (artificial graphite, graphitization degree 95%), polyacrylic acid (weight average molecular weight Mw = 3500), and single-walled carbon nanotubes were mixed at a mass ratio of 95:4.5:0.5. Deionized water was added as a solvent, and the mixture was stirred to prepare a negative electrode slurry with a solid content of 42wt%. The negative electrode slurry was then coated onto both surfaces of a 6μm thick copper foil negative electrode current collector, with a coating mass of 40mg / 1540.25mm. 2 The first negative electrode material layer is formed by drying at 100℃. This layer consists of graphite (artificial graphite, graphitization degree 95%), silicon-carbon composite material (Dv50 = 8.6μm, silicon deposition amount 50%), and lithium lanthanum zirconium oxide fiber (length 15μm, diameter 150nm, specific surface area 300m²). 2 A mixture of polyacrylic acid (Mw = 3500) and single-walled carbon nanotubes in a mass ratio of 35:53.33:6.67:4.5:0.5 was thoroughly mixed, and deionized water was added and stirred to prepare a negative electrode slurry with a solid content of 42wt%. This slurry was then coated onto the surfaces of the two first negative electrode material layers furthest from the copper foil, with a coating mass of 60mg / 1540.25mm. 2 After drying at 100℃, a second negative electrode material layer is formed. The negative electrode material layer is then cold-pressed until its compaction density is 1.6 × 10⁻⁶. 3 kg / m 3 The negative electrode sheet with a size of 1000mm×80mm is obtained by slitting.
[0129] <Preparation of the positive electrode>
[0130] Lithium cobalt oxide (CCO), conductive carbon black (Super P), and polyvinylidene fluoride (PVDF, Mw = 600,000) were mixed in a mass ratio of 97.8:1.4:0.8. N-methylpyrrolidone (NMP) was added as a solvent, and the mixture was stirred under vacuum until a homogeneous CCO slurry with a solid content of 72 wt% was obtained. The CCO slurry was uniformly coated onto one surface of a 10 μm thick aluminum foil current collector and dried at 85°C to obtain a single-sided CCO electrode with a 90 μm thick CCO active material layer. The above steps were then repeated on the other surface of the aluminum foil to obtain a double-sided CCO electrode with a CCO active material layer. The CCO material layer was cold-pressed to a compaction density of 4.0 × 10⁻⁶. 3 kg / m 3 Cut the sheet and weld the positive electrode tabs to obtain a positive electrode sheet with a specification of 990mm×76mm.
[0131] <Preparation of Electrolyte>
[0132] In a dry argon atmosphere, non-aqueous solvents ethylene carbonate (EC) and dimethyl carbonate (DMC) were mixed uniformly at a mass ratio of 1:1, and lithium salt lithium hexafluorophosphate was added and stirred until homogeneous to obtain the electrolyte. The lithium salt concentration was 1 mol / L.
[0133] <Septum>
[0134] A porous polyethylene (PE) membrane with a thickness of 8 μm was used as the diaphragm.
[0135] <Preparation of Secondary Batteries>
[0136] The separator, positive electrode, separator, and negative electrode are stacked in sequence and wound to obtain the electrode assembly. The electrode assembly is placed in an aluminum-plastic film packaging bag, and after dehydration at 80°C, electrolyte is injected and the battery is sealed. After processes such as formation, degassing, and shaping, a secondary battery is obtained.
[0137] In Example 1-1, based on the total mass of the first negative electrode material layer and the second negative electrode material layer, the mass percentage of ceramic nanofibers in the second negative electrode material layer is W3, the mass percentage of silicon-carbon composite material is W6, the mass percentage of silicon is W4, and the mass percentage of graphite is W7; based on the total mass of the first negative electrode material layer and the second negative electrode material layer, the mass percentage of graphite in the first negative electrode material layer is W8, and the mass percentage of silicon-carbon composite material is W9.
[0138] Among them, W3, W4, W6, W7, and W8 can be calculated according to the following formula:
[0139] W3=K1×CW2 / (CW1+CW2) Relationship (1)
[0140] W6=K2×CW2 / (CW1+CW2) Relationship (2)
[0141] W4 = W8 × A1 (Relationship 3)
[0142] W7=K3×CW2 / (CW1+CW2) Relationship (4)
[0143] W8=K4×CW1 / (CW1+CW2) Relationship (5)
[0144] When the first negative electrode material layer includes a silicon-carbon composite material, W9 and W5 can be calculated using the following formula:
[0145] W9=K5×CW1 / (CW1+CW2) Relationship (6)
[0146] W5 = W9 × A2 (7)
[0147] Wherein, K1 represents the mass percentage of ceramic nanofibers in the second negative electrode material layer based on its mass; K2 represents the mass percentage of silicon-carbon composite material in the second negative electrode material layer based on its mass; K3 represents the mass percentage of graphite in the second negative electrode material layer based on its mass; K4 represents the mass percentage of graphite in the first negative electrode material layer based on its mass; K5 represents the mass percentage of silicon-carbon composite material in the first negative electrode material layer based on its mass; A1 represents the amount of silicon deposited in the silicon-carbon composite material in the second negative electrode material layer; A2 represents the amount of silicon deposited in the silicon-carbon composite material in the first negative electrode material layer; CW1 represents the coating quality of the first negative electrode material layer; and CW2 represents the coating quality of the second negative electrode material layer.
[0148] Taking Example 1-1 as an example, the following can be calculated according to the above relationship:
[0149] W3=6.67%×60 / (40+60)=4%,
[0150] W6=53.33%×60 / (40+60)=32%,
[0151] W4 = 32% × 50% = 16%,
[0152] W7=35%×60 / (40+60)=21%,
[0153] W8=95%×40 / (40+60)=38%,
[0154] W9=0,
[0155] W5 = 0.
[0156] It should be understood that, based on the total mass of the first and second negative electrode material layers, the mass percentage of graphite in the negative electrode material layer is the sum of W7 and W8. For example, in Example 1-1, based on the total mass of the first and second negative electrode material layers, the mass percentage of graphite in the negative electrode material layer is 59%.
[0157] Examples 1-2 to Examples 1-9:
[0158] Except for adjusting the ratio of graphite, silicon-carbon composite material and lithium lanthanum zirconium oxide fiber in the second negative electrode material layer to make W3, W6, W4 and W7 change according to Table 1-1, the rest are the same as in Example 1-1.
[0159] The ratio of graphite, silicon-carbon composite material and lithium lanthanum zirconium oxygen fiber in the second negative electrode material layer can be calculated based on the above-mentioned formulas (1) to (7) and W3, W6, W4 and W7 shown in Table 1-1. They will not be listed one by one here.
[0160] Examples 1-10:
[0161] Except for the changes described below, everything else is the same as in Example 1-1.
[0162] The second anode material layer consists of graphite (artificial graphite, graphitization degree 95%), silicon-carbon composite material (Dv50 = 8.6 μm, silicon deposition rate 69.5%), and lithium lanthanum zirconium oxide fiber (length 15 μm, diameter 150 nm, specific surface area 300 m²). 2 The composition of the nanoparticles is: polyacrylic acid (Mw = 3500), and single-walled carbon nanotubes, in a mass ratio of 0:90:5:4.5:0.5. CW1 = 20 mg / 1540.25 mm. 2 CW2 = 80 mg / 1540.25 mm 2 .
[0163] Correspondingly, W3 = 5% × 80 / (20 + 80) = 4%.
[0164] W6=90%×80 / (20+80)=72%,
[0165] W4=72%×69.5%=50%,
[0166] W7=0%×80 / (20+80)=0%,
[0167] W8=95%×20 / (20+80)=19%.
[0168] Examples 1-11:
[0169] Except for the changes described below, everything else is the same as in Example 1-1.
[0170] The second anode material layer consists of graphite (artificial graphite, graphitization degree 95%), silicon-carbon composite material (Dv50 = 8.6 μm, silicon deposition amount 50%), and lithium lanthanum zirconium oxide fiber (length 15 μm, diameter 150 nm, specific surface area 300 m²). 2 The composition of the components is polyacrylic acid (Mw = 3500), and single-walled carbon nanotubes, in a mass ratio of 15:64:16:4.5:0.5. CW1 = 75 mg / 1540.25 mm. 2 CW2 = 25mg / 1540.25mm 2 .
[0171] Correspondingly, W3 = 16% × 25 / (75 + 25) = 4%.
[0172] W6=64%×25 / (75+25)=16%,
[0173] W4 = 16% × 50% = 8%,
[0174] W7=15%×25 / (75+25)=3.75%,
[0175] W8=95%×75 / (75+25)=71.25%.
[0176] Examples 1-12 to Examples 1-17:
[0177] Except for adjusting the length, diameter, and specific surface area of the lithium lanthanum zirconium oxide fiber according to Table 1-1, the rest is the same as in Example 1-1.
[0178] Examples 1-18 to Examples 1-21:
[0179] Except for adjusting the specific surface area of the lithium lanthanum zirconium oxide fiber according to Table 1-1, the rest is the same as in Example 1-1.
[0180] Examples 1-22 to 1-25:
[0181] Except for adjusting the type of ceramic nanofibers according to Table 1-1, the rest is the same as in Example 1-1.
[0182] Examples 1-26
[0183] Except for replacing the silicon-carbon composite material in the negative electrode with micron-sized silicon, and adjusting the ratio of graphite, micron-sized silicon and lithium lanthanum zirconium oxide fiber in the second negative electrode material layer so that W3, W6, W4 and W7 are varied according to Table 1-1, the rest are the same as in Example 1-1.
[0184] It should be noted that when micron-sized silicon is used as the silicon-containing material, W4 is the same as W7.
[0185] Comparative Example 1-1:
[0186] Except for the absence of ceramic nanofibers in the second negative electrode material layer, the rest is the same as in Example 1-1.
[0187] Comparative Examples 1-2:
[0188] Except that the ceramic nanofibers added to the second negative electrode material layer were replaced with polyamide fibers, and the specific surface area of the polyamide fibers was 120 m². 2 Except for / g, the rest is the same as in Example 1-1.
[0189] For the test data of each set of embodiments and comparative examples in Table 1-1, please refer to Table 1-2.
[0190] Table 1-1
[0191]
[0192]
[0193]
[0194] Table 1-2
[0195]
[0196]
[0197] Referring to Examples 1-1 to 1-25, when the negative electrode material layer has a double-layer structure and the second negative electrode material layer includes silicon-carbon composite material, adding ceramic nanofibers to the second negative electrode material layer can help reduce the risk of lithium plating on the negative electrode sheet and improve the capacity decay problem of the secondary battery.
[0198] Figure 2 The images show SEM images of the negative electrode sheet prepared in Example 1-1 at different magnifications.
[0199] like Figure 2 As shown in (a), the white horizontal bar in the middle represents the negative electrode current collector. The upper and lower sides of the negative electrode current collector are the negative electrode material layers. The dark gray area in the negative electrode material layer represents graphite, and the light gray spherical particles in the negative electrode material layer represent silicon-carbon composite materials. Figure 2 As shown in (a), graphite is distributed on the side closer to the negative electrode current collector, but there is no silicon-carbon composite material; this region corresponds to the first negative electrode material layer. Graphite and silicon-carbon composite material are distributed on the side farther from the negative electrode current collector; this region corresponds to the second negative electrode material layer. It can be seen that, as... Figure 2 The negative electrode material layer shown in (a) is a double-layer structure.
[0200] like Figure 2 As shown in (b), spherical particles represent silicon-carbon composite materials, sheet-like or blocky structures represent graphite, and filamentous structures represent ceramic nanofibers. Figure 2 As shown in (b), ceramic nanofibers intertwine and entangle with each other in the voids formed by silicon-carbon composite material / graphite to form an impregnation network.
[0201] In this way, the interwoven and entangled structures form a wetting network, which effectively fills and connects the pores inside the second negative electrode material layer, maintaining the integrity of the lithium-ion transport pathway and improving the wettability of the electrolyte in the negative electrode sheet. This helps to reduce the risk of lithium plating on the negative electrode sheet in the secondary battery and improve the capacity decay problem of the secondary battery.
[0202] Referring to Comparative Example 1-1, without adding any nanofibers to the second negative electrode material layer, the volume expansion of the silicon-carbon composite material leads to insufficient wettability of the electrolyte, thus obstructing the lithium-ion transport path. Combined with the test data in Table 2-1, this specifically manifests as a higher R2 in the secondary battery, poor electrolyte absorption rate of the electrode, a high risk of lithium plating on the negative electrode, and poor cycle performance of the secondary battery.
[0203] Referring to Comparative Examples 1-2, while adding polyamide fibers to the second negative electrode material layer improves lithium plating risk and cycle performance to some extent compared to Comparative Example 1-1, the improvement effect is still somewhat less than that of Examples 1-1 to 1-25. This is because the ceramic nanofibers in Examples 1-1 to 1-25 possess lithium-ion conductivity or can spontaneously react to generate lithium-ion conductive substances during charging. In this way, lithium ions can migrate rapidly along the lattice structure of the ceramic nanofibers, using the ceramic nanofibers themselves as lithium-ion transport channels and maintaining the integrity of the lithium-ion transport pathway. Therefore, compared to adding polyamide fibers, which do not possess lithium-ion conductivity, it is more beneficial to reduce the lithium plating risk of the negative electrode in the secondary battery and improve the capacity decay problem of the secondary battery.
[0204] Referring to Examples 1-2, 1-4, 1-5, 1-8, and 1-9, when the silicon content (W4) in the second negative electrode material layer is the same, the maximum non-analytical ratio and the number of cycle jumps increase simultaneously with the increase of W3. When W3 reaches 4%, the number of cycle jumps further increases, but the maximum non-analytical ratio no longer increases further. When W3 reaches 8%–10%, the maximum non-analytical ratio and the number of cycle jumps begin to decrease. This is because although the addition of a large amount of ceramic nanofibers improves electrolyte wettability, excessive addition of ceramic nanofibers results in excessive occupancy of the pores within the electrode, leading to a decrease in the porosity of the electrode and consequently affecting the electrolyte absorption rate. Therefore, W3 can be controlled to be 0.5%–8%. Preferably, W3 can be 3.2%–8%; more preferably, W3 can be 3.2%–4%.
[0205] Referring to Examples 1-1, 1-10, and 1-11, when the mass percentage W3 of ceramic nanofibers in the second negative electrode material layer is the same, as W4 increases, the maximum non-analytical rate and the number of cycle drops decrease simultaneously, but the volumetric energy density increases. Considering the maximum non-analytical rate, the number of cycle drops, and the volumetric energy density, W4 can preferably be 8% to 50%. When W4 is below 8%, the volumetric energy density of the secondary battery is too low; when W4 is above 50%, it is not conducive to reducing the analytical risk of the negative electrode sheet and is not conducive to improving cycle performance.
[0206] Referring to Examples 1-1 to 1-11, when 0.02 ≤ W3 / W4 ≤ 0.5, the amount of ceramic nanofibers added matches the silicon content in the second negative electrode material layer, forming a suitable wetting network structure in the second negative electrode material layer. This is beneficial for reducing the risk of lithium-ion degradation in the negative electrode sheet and improving the problem of rapid capacity decay in the secondary battery. When W3 / W4 < 0.02, such as in Example 2-2, compared with the pore volume generated by the volume expansion of the silicon-containing material in the second negative electrode material layer, the amount of ceramic nanofibers added is too small to form an interconnected wetting network in the relatively large pore volume. This makes it difficult to play a role in promoting lithium-ion transport. Therefore, the maximum non-degradation rate and the number of cycle drops are not ideal. When W3 / W4 > 0.5, for example in Examples 2-9, compared to the pore volume generated by the volume expansion of silicon-containing materials in the second negative electrode material layer, the amount of ceramic nanofibers added is too large. Too many ceramic nanofibers occupy too many pores in the second negative electrode material layer, resulting in insufficient electrolyte entering the pores, which hinders the transport of lithium ions. Therefore, the maximum non-chemical rate and the number of cycle drops are not ideal, which is not conducive to reducing the chemical risk of the negative electrode sheet and is not conducive to improving the problem of rapid capacity decay of the secondary battery.
[0207] Referring to Examples 1-12 to 1-17, the length of the ceramic nanofibers was adjusted to 5–30 μm, the diameter to 50–300 nm, and the specific surface area to 100–1000 m². 2 / g, which is beneficial to promote the interweaving and entanglement of ceramic nanofibers to form an impregnation network, thereby reducing the risk of lithium plating on the negative electrode in the secondary battery and improving the capacity decay problem of the secondary battery.
[0208] Referring to Examples 1-14, the specific surface area of the regulated ceramic nanofibers with a diameter of 20 nm reached 2225 m². 2 Although a high specific surface area is beneficial to improving the wettability of the electrolyte in the negative electrode, the length of the ceramic nanofibers is only 2μm. The ceramic nanofibers with too short a length are difficult to intertwine and form a wettability network, which leads to a decrease in the highest non-lithiation rate and cycle performance.
[0209] Referring to Examples 1-18 to 1-21, when the length and diameter of the ceramic nanofibers are appropriate, increasing the specific surface area of the ceramic nanofibers is beneficial for improving the wettability of the electrolyte in the negative electrode and thus improving the cycle performance of the secondary battery. However, increasing the specific surface area of the ceramic nanofibers also increases the number of side reaction sites between the electrolyte and the material within the negative electrode. When the specific surface area of the ceramic nanofibers is too large, the excessive number of side reaction sites between the electrolyte and the material within the negative electrode will, conversely, worsen the cycle performance of the secondary battery. For example, referring to Examples 1-19 and 1-21, when the specific surface area of the ceramic nanofibers increases from 1000 m² / h, the increase in the specific surface area of the ceramic nanofibers can lead to a decrease in the specific surface area of the negative electrode. 2 / g increased to 1200m 2 At a specific surface area of 100–1000 m² / g, the cycle performance of the secondary battery actually decreases. Therefore, preferably, the specific surface area of the ceramic nanofibers is 100–1000 m² / g. 2 / g.
[0210] Referring to Examples 1-22 to 1-25, the stronger the lithium-ion conductivity of the selected ceramic nanofibers, the more beneficial it is to reduce the risk of lithium plating on the negative electrode in the secondary battery and to improve the capacity decay problem of the secondary battery.
[0211] Referring to Examples 1-1 and 1-26, the silicon-containing material can be a silicon-carbon composite material or micron-sized silicon. When micron-sized silicon is used, it is more beneficial to reduce the risk of lithium plating on the negative electrode. When a silicon-carbon composite material is used, it is more beneficial to improve the capacity decay problem of the secondary battery and increase the volumetric energy density.
[0212] Second set of examples and comparative examples: preparation of secondary batteries in which the negative electrode material layer in the negative electrode sheet is a single-layer structure.
[0213] Example 2-1
[0214] Except for the preparation method of the negative electrode sheet, Implementation 2-1 is the same as Implementation 1-1.
[0215] <Preparation of Negative Electrode Sheets>
[0216] Artificial graphite (95% graphitization), silicon-carbon composite material (Dv50 = 8.6 μm, silicon deposition rate 50%), and lithium lanthanum zirconium oxide ceramic fiber (length 15 μm, diameter 150 nm, specific surface area 300 m²) were used. 2 / g, lithium-ion conductivity 5.4×10 -4S / cm), polyacrylic acid (weight average molecular weight Mw = 3500), and single-walled carbon nanotubes were mixed in a mass ratio of 58.2:32:4.8:4.5:0.5, with deionized water added as a solvent, and stirred to prepare a negative electrode slurry with a solid content of 42wt%. The negative electrode slurry was then coated onto both surfaces of the negative electrode current collector copper foil, with a coating mass of 100mg / 1540.25mm. 2 Afterwards, it is dried at 100℃ and cold-pressed until the compaction density of the negative electrode material layer is 1.6×10⁻⁶. 3 kg / m 3 The negative electrode sheet with a size of 1000mm×80mm is obtained by slitting.
[0217] Examples 2-2 to 2-11:
[0218] Except for adjusting the mass percentages of graphite, silicon-carbon composite material, and lithium lanthanum zirconium oxide fiber in the negative electrode material layer according to Table 2-1, the rest is the same as in Example 2-1. In Example 2-10, the silicon deposition amount in the silicon-carbon composite material is 66.7%.
[0219] Comparative Example 2-1:
[0220] Except for the absence of ceramic nanofibers in the negative electrode material layer, the rest is the same as in Example 2-1.
[0221] Comparative Example 2-2:
[0222] In addition to replacing the ceramic nanofibers added to the negative electrode material layer with polyamide fibers, the specific surface area of the polyamide fibers is 120 m². 2 Except for / g, the rest is the same as in Example 2-1.
[0223] For the test data of each set of embodiments and comparative examples in Table 2-1, please refer to Table 2-2.
[0224] Table 2-1
[0225]
[0226] Table 2-2
[0227]
[0228]
[0229] Referring to Examples 2-1 to 2-11, when the negative electrode material layer is a single-layer structure and includes silicon-carbon composite material, adding ceramic nanofibers to the negative electrode material layer can help reduce the risk of lithium plating on the negative electrode sheet in the secondary battery and improve the capacity decay problem of the secondary battery.
[0230] Figure 3 The images show SEM images of the negative electrode sheet prepared in Example 2-1 at different magnifications.
[0231] like Figure 3 As shown in (a), the white horizontal bar in the middle represents the negative electrode current collector. The upper and lower sides of the negative electrode current collector are the negative electrode material layers. The dark gray area in the negative electrode material layer represents graphite, and the light gray spherical particles in the negative electrode material layer represent silicon-carbon composite materials. Figure 3 As shown in (a), silicon-carbon composite materials are distributed on both the side of the negative electrode material layer closest to the negative electrode current collector and the side furthest from the negative electrode current collector. It can be seen that, as... Figure 3 The negative electrode material layer shown in (a) is a single-layer structure.
[0232] like Figure 3 As shown in (b), spherical particles represent silicon-carbon composite materials, sheet-like or blocky structures represent graphite, and filamentous structures represent ceramic nanofibers. Figure 3 As shown in (b), ceramic nanofibers intertwine and entangle with each other in the voids formed by silicon-carbon composite material / graphite to form an impregnation network.
[0233] In this way, the interwoven and entangled structures form a wetting network, which effectively fills and connects the pores inside the negative electrode material layer with the electrolyte, maintaining the integrity of the lithium-ion transport pathway and improving the wettability of the electrolyte in the negative electrode sheet. This helps to reduce the risk of lithium plating on the negative electrode sheet in secondary batteries and improve the capacity decay problem of secondary batteries.
[0234] Referring to Comparative Example 2-1, without adding any nanofibers to the negative electrode material layer, the volume expansion of the silicon-carbon composite material leads to insufficient wettability of the electrolyte, thus obstructing the lithium-ion transport path. Combined with the test data in Table 2-2, it can be seen that the lithium plating problem on the negative electrode sheet is quite serious.
[0235] Referring to Comparative Example 2-2, while adding polyamide fibers to the negative electrode material layer improves the lithium plating risk to some extent compared to Comparative Example 2-1, it still falls short of the improvement effect in Examples 2-1 to 2-11. This is because the ceramic nanofibers in Examples 2-1 to 2-11 possess lithium-ion conductivity or can spontaneously react to generate lithium-ion conductive substances during charging. In this way, lithium ions can migrate rapidly along the lattice structure of the ceramic nanofibers, using the ceramic nanofibers themselves as lithium-ion transport channels and maintaining the integrity of the lithium-ion transport pathway. Therefore, compared to adding polyamide fibers, which lack lithium-ion conductivity, it is more beneficial to reduce the lithium plating risk of the negative electrode in the secondary battery and improve the capacity decay problem of the secondary battery.
[0236] Referring to Examples 2-1 to 2-7, when W1 is 1% to 10%, it is beneficial to reduce the risk of lithium plating on the negative electrode and to improve the cycle performance of the secondary battery. When W1 is too low, such as in Example 2-2, insufficient ceramic nanofibers are not enough to form a wetting network, making it difficult to exert a wetting effect, which is not conducive to reducing the risk of lithium plating on the negative electrode and improving the cycle performance of the secondary battery. When W1 is too high, such as in Example 2-7, due to the excessive addition of ceramic nanofibers, the ceramic nanofibers occupy too much of the pores in the electrode, resulting in a decrease in the porosity of the electrode, which in turn affects the liquid absorption rate and is also not conducive to reducing the risk of lithium plating on the negative electrode and improving the cycle performance of the secondary battery.
[0237] Referring to Examples 2-1 to 2-11, when 0.06 ≤ W1 / W2 ≤ 0.8, it is beneficial for reducing the risk of lithium plating on the negative electrode and improving the capacity decay problem of the secondary battery, as well as for increasing the volumetric energy density of the secondary battery. When W1 / W2 < 0.06, as in Example 2-2, compared with the pore volume generated by the volume expansion of silicon-containing materials, the amount of ceramic nanofibers added is too small to form an interconnected wetting network within the relatively large pore volume, making it difficult to play a role in promoting lithium-ion transport and hindering the reduction of the risk of lithium plating on the negative electrode in the secondary battery. When W1 / W2 > 0.8, as in Examples 2-9, the content of silicon-containing materials in the negative electrode material layer is relatively small, which is not conducive to increasing the volumetric energy density of the secondary battery.
[0238] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and not to limit them; under the concept of this application, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of different aspects of this application as described above, which are not provided in detail for the sake of brevity; although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the foregoing embodiments, or make equivalent substitutions for some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
Claims
1. A negative electrode sheet, characterized in that, The negative electrode sheet includes a negative current collector and a negative electrode material layer formed on at least one surface of the negative current collector, wherein the negative electrode material layer includes silicon-containing material and ceramic nanofibers.
2. The negative electrode sheet according to claim 1, characterized in that, Based on the mass of the negative electrode material layer, the mass percentage of the ceramic nanofibers is 0.5% to 10%.
3. The negative electrode sheet according to claim 2, characterized in that, The negative electrode material layer is a single-layer coating. Based on the mass of the negative electrode material layer, the mass percentage of the ceramic nanofiber is W1, where W1 is 1% to 10%.
4. The negative electrode sheet according to claim 3, characterized in that, The mass percentage of silicon in the negative electrode material layer is W2, where 0.06 ≤ W1 / W2 ≤ 0.
8.
5. The negative electrode sheet according to claim 2, characterized in that, The negative electrode material layer includes a first negative electrode material layer and a second negative electrode material layer. Along the thickness direction of the negative electrode sheet, the first negative electrode material layer is disposed between the negative electrode current collector and the second negative electrode material layer. The second negative electrode material layer includes silicon-containing materials and ceramic nanofibers; Based on the total mass of the first negative electrode material layer and the second negative electrode material layer, the mass percentage of ceramic nanofibers in the second negative electrode material layer is W3, where W3 is 0.5% to 8%.
6. The negative electrode sheet according to claim 5, characterized in that, Based on the total mass of the first negative electrode material layer and the second negative electrode material layer, the mass percentage of silicon in the second negative electrode material layer is W4, and 0.02≤W3 / W4≤0.
5.
7. The negative electrode sheet according to claim 6, characterized in that, The negative electrode active material in the first negative electrode material layer includes one or more of graphite, hard carbon, and lithium titanate; the negative electrode active material in the second negative electrode material layer includes one or more of silicon-carbon composite material, silicon-oxygen composite material, micron-sized silicon, and nano-sized silicon; or, the negative electrode active material in the second negative electrode material layer includes one or more of silicon-carbon composite material, silicon-oxygen composite material, micron-sized silicon, and nano-sized silicon, as well as one or more of graphite, hard carbon, and lithium titanate.
8. The negative electrode sheet according to claim 1, characterized in that, The negative electrode active material in the negative electrode material layer includes one or more of silicon-carbon composite materials, silicon-oxygen composite materials, micron-sized silicon, and nano-sized silicon; or, the negative electrode active material in the negative electrode material layer includes one or more of silicon-carbon composite materials, silicon-oxygen composite materials, micron-sized silicon, and nano-sized silicon, as well as one or more of graphite, hard carbon, and lithium titanate.
9. The negative electrode sheet according to any one of claims 1 to 8, characterized in that, The ceramic nanofibers satisfy at least one of the following: (1) The length of the ceramic nanofibers is 5 to 30 μm; (2) The diameter of the ceramic nanofibers is 50-300 nm; (3) The specific surface area of the ceramic nanofibers is 100-1000 m². 2 / g; or (4) The lithium-ion conductivity of the ceramic nanofibers is greater than or equal to 3 × 10⁻⁶. -8 S / cm.
10. The negative electrode sheet according to any one of claims 1 to 8, characterized in that, The ceramic nanofibers are selected from at least one of the following: alumina nanofibers, titanium dioxide nanofibers, zinc oxide nanofibers, vanadium oxide nanofibers, molybdenum oxide nanofibers, zirconium oxide nanofibers, aluminum hydroxide nanofibers, silicon carbide nanofibers, boron nitride nanofibers, lithium lanthanum zirconium oxide nanofibers, lithium lanthanum zirconium niobium oxide nanofibers, lithium lanthanum titanium oxide nanofibers, lithium titanium aluminum phosphate nanofibers, and lithium germanium aluminum phosphate nanofibers.
11. A secondary battery, characterized in that, It includes the negative electrode sheet as described in any one of claims 1 to 10.
12. An electronic device, characterized in that, Includes the secondary battery as described in claim 11.
